Methodological guidelines designed to improve the quality of research on cross-country skiing - Pellegrini, B.; Sandbakk, O.; Stöggl, T.; Supej, M.; Ortenblad, N.; Schürer, A.; Steiner, T.; Lunina, A.; Manhard, C.; Liu, H.; Ohtonen, O.; Zoppirolli, C.; et al. (Journal of Science in Sport and Exercise, 2021)
Cross-country (XC) ski races involve a variety of formats, two different techniques and tracks with highly variable topography and environmental conditions. In addition, XC skiing is a major component of both Nordic combined and biathlon competitions. Research in this area, both in the laboratory and field, encounters certain difficulties that may reduce the reliability and validity of the data obtained, as well as complicate comparisons between studies. Here, 13 international experts propose specific guidelines designed to enhance the quality of research and publications on XC skiing, as well as on the biathlon and Nordic combined skiing. We consider biomechanical (kinematic, kinetic and neuromuscular) and physiological methodology (at the systemic and/or muscle level), providing recommendations for standardization/control of the experimental setup. We describe the types of measuring equipment and technology that are most suitable in this context. Moreover, we also deal with certain aspects of nomenclature of the classical and skating sub-techniques. In addition to enhancing the quality of studies on XC skiing, Nordic combined and biathlon, our guidelines should also be of value for sport scientists and coaches in other disciplines where physiological and/or biomechanical measurements are performed in the laboratory and/or outdoors.